Effect of Prebiotic, Probiotic Bacteria and Symbiotic Diets Containing Bacillus Coagulans and Gum Arabic on Lipid Profile in Hypercholesterolemic Rats - Altawari, Hanan (International Journal of Food Sciences, 2024)
Purpose: Hypercholesterolemia poses a significant challenge for numerous communities and healthcare professionals because of the association between cardiovascular conditions and dyslipidemia. The objective of this research was to assess the impact of prebiotics, probiotics, as well as a diet incorporating Bacillus coagulants and gum Arabic on blood lipid levels in hypercholesterolemic rats. Methodology: In order to create an antiseptic solution, acquire the organic substance known as gum Arabic. Thirty-five male Albino rats (170 ± 5 g) were feeding a prepared diet includes supplemented cholesterol to raise the levels of cholesterol. Mice were divided to 5 groups (n = 7). Group 1: simple diet (negative control), the other 4 groups were assigned for a hypercholesterolemia diet comprising 25% lard and 2% cholesterol for 6 weeks in order to increase fat cholesterol in rats. Group 2: (positive control), Group 3: fed with a supplement including 5% gum Arabic (prebiotic), Group 4: fed with a dietary supplement comprising coagulase spores, Group 5: assigned for a simple meal. It was supplemented with 5% daily gum Arabic and Bacillus coagulants spores (symbiotic). Results: Triglyceride levels and total cholesterol (mg/dL) were improved (P<0.05). In (advantageous manipulate) fed a simple diet (B.D.), compared with (poor manipulate). Unique Contribution to theory, Practice and Policy: The Anti-Inflammatory Theory and the concept of prebiotics usage to decrease cholesterol and minimize its absorption. This shows that the concept used has been validated. The satisfactory results which confirmed the extreme spread variations with the poor manipulate organization had been done within side the hypercholesterolemia organizations include with Gum Arabic (GA5%), where the best indicated a fee recorded (28.54 ± 3. seventy one mg/dL), which transferred into the poor manipulate (36.33 ± 5.00 mg/dL). As for the organizations that took B. coagulants and GA 5% + B. coagulants, a lower in LDL-c, (VLDL-c), levels of AST and AST, and the satisfactory outcome documented and directed within side of the organization GA 5% + B.Coagulants. Histological checkups furthermore confirmed that the liver sections inside the 5th organization established a regular structure, also the liver cells mild degeneration. CONCLUSION: The satisfactory final outcome indicated within side the organization of GA 5%+ B. coagulants remedy organization compared with the opposite organizations.